The anti-melanoma activity of dinaciclib, a cyclin-dependent kinase inhibitor, is dependent on p53 signaling. - Brijal M Desai; Jessie Villanueva; Thierry-Thien K Nguyen; Mercedes Lioni; Min Xiao; Jun Kong; Clemens Krepler; Adina Vultur; Keith T Flaherty; Katherine L Nathanson; Keiran S M Smalley; Meenhard Herlyn (PLoS ONE, 2013)
Although cyclin dependent kinase (CDK)-2 is known to be dispensable for the growth of most tumors, it is thought to be important for the proliferation of melanoma cells, where its expression is controlled by the melanocyte-lineage specific transcription factor MITF. Treatment of a panel of melanoma cells with the CDK inhibitor dinaciclib led to a concentration-dependent inhibition of growth under both 2D adherent and 3D organotypic cell culture conditions. Dinaciclib targeted melanoma cell lines regardless of cdk2 or MITF levels. Inhibition of growth was associated with a rapid induction of G2/M cell arrest and apoptosis. Treatment of human melanoma mouse xenografts with dinaciclib led to tumor regression associated with reduced retinoblastoma protein phosphorylation and Bcl-2 expression. Further mechanistic studies revealed that dinaciclib induces p53 expression whilst simultaneously downregulating the expression of the anti-apoptotic factors Mcl-1 and XIAP. To clarify the role of p53 activation in the dinaciclib-induced cell death, we generated melanoma cell lines in which p53 expression was knocked down using a shRNA lentiviral vector. Knockdown of p53 completely abolished the induction of apoptosis seen following dinaciclib treatment as shown by a lack of annexin-V staining and caspase-3 cleavage. Altogether, these data show that dinaciclib induces apoptosis in a large panel of melanoma cell lines through a mechanism requiring p53 expression.